PENGARUH ROTASI AUDIT, KOMITE AUDIT DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Jevelyn Winda L. dan Paul E. Sudjiman (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2021)
As for the purpose of this research that the author made is to determine the effect of audit rotation, audit committees and auditor reputation on the audit quality by using data from annual reports of manufacturing companies in the textile and garment sub sector which exist on Indonesia Stock Exchange during 2018-2020 period and the sample was done by using purposive sampling method of 54 data of 18 companies over a 3-years period and the analytical method by using logistic regression analysis from SPSS 24 tools. The results of this research and analysis concluded that audit rotation, audit committees and auditor reputation have no significant effect on the audit quality.